Anti-dense fine speckled (DFS) antibody: its staining pattern in indirect immunofluorescence and its clinical relevance - Karahan Samet; Emre Şerife; Hörmet-Öz Hatice T. (Sciendo, 2022)
Background: Dense fine speckled (DFS) pattern is defined by very intense, heterogeneous speckled staining of nucleoplasms of interphase HEp-2 cells and chromosomal areas of metaphase cells. The association of Anti-DFS70 and rheumatologic signs, symptoms, and diagnosis were evaluated.